Development of microwave level detection of multilayer liquids in biodiesel production - Seresht, Mahmoud Homaiee (2011)
Biodiesel is a fuel which is produced from a reaction between a type of fat and alcohol in the presence of a catalyst to accelerate the reaction. The production process is divided into two main parts: transesterification and washing process. After transestrification, glycerin and some residuals were produced and settled under the biodiesel while water settled down under the biodiesel after the washing process. Therefore, there is a need to determine the biodiesel-glycerin interface after transesterification process and biodiesel-water after washing process. These steps are important for accurate release of glycerin from the container in order to prevent wasting of biodiesel and to retain good quality of biodiesel. Microwave as a method for level measurement can help to detect the position of each layer. Our objectives are based on the moving up and down of an X-band (10.70 GHz) microwave sensor inside the container to measure the level of each layer. Simulation of the theoretical principles of various liquid detection and determination of the purity of washed biodiesel are achieved through the comparison between dielectric constants of materials. The microwave detection system is monitored by a PC through a program in LABVIEW 8.5 environment which receive data from the sensor, control stepper motor movement and analyze and plot the final output based on the amplitude of the reflected wave and distance. The theoretical principles of the detection of multilayer system are simulated by MATLAB program for detection of glycerin-biodiesel after transesterification and water-biodiesel after the washing processes separately. The behavior of the reflected was studied at a distance of 160 mm. Comparing the simulation results and level measurement shows the experimental results are in good agreement with theoretical values. As our main work is based on the changes of the permittivity elements, it is measured after each time of the washing process through VNA (Vector Network Analyzer) and recalculated from the reflection profile again by the present mathematical method. This method calculates the dielectric constant through the relation between elements of permittivity, phase constant and attenuation.The error between these methods is about ±0.6. By comparing dielectric of washed biodiesel at each washing with pure biodiesel, it is possible to determine the purity of biodiesel. Generally the results show the developed system be able to give the accuracy of level detection of about ±0.1 mm and for the liquid height of 160 mm, it takes around 18 minutes to complete the measurement. In conclusion, the software based design has been developed which can determine the interface level and purity of biodiesel furthermore. It is flexible, easy to control, low cost and user friendly.